A DISCURSIVE CONSTRUCTION OF IDENTITIES THROUGH VERBAL HUMOR - Hoa, Nguyen (VNU Journal of Foreign Studies; Vol 33 No 3DO - 10.25073/2525-2445/vnufs.4151, 2017)
This study focuses on how verbal humor can discursively construct identities, grounded in the assumption of social constructionism that identity is not given, but is constructed in social practice (Foucault, 1984), or discourse practices (Fairclough, 2001). I exploit a mix of Critical Discourse Analysis (CDA) methods and Gricean pragmatics in the analysis of implicature-generated humor occurring in a speech delivered in the political context of a presidential election. The findings show that verbal humor (created through the use of language in contexts of situation) is not just for “fun” or “humor”, but also for performing a variety of pragmatic functions such as developing social relations, creating solidarity, or the construction of identities in socio-political contexts (presidential election), which is consistent with other research projects concerning the function of verbal humor. I have made every effort to conceal the identity of the individuals to the possible extent in ways that do not hinder comprehension. The two main characters are named John and Mary. Three individual are coded X, Y, and Z as they appear in the remarks. The election happened in country A.